The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1557/jmr.1993.0962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single crystal substrates on the growth and properties of superconducting Tl2Ba2CaCu2O8 films

Abstract: Superconducting Tl 2 Ba 2 CaCu2O8 films were prepared by a two-step postdeposition anneal process under identical conditions on a number of single crystal substrates: (100) LaA10 3 , (100) NdGaO 3 , (100) LaGaO 3 , (100) SrTiO 3 , (100) MgO, and (0001) A1 2 O 3 . The properties of the resulting Tl 2 Ba 2 CaCu 2 0 8 films were strongly dependent on the substrate. Films on all substrates were predominantly c-axis oriented. Films prepared on LaA10 3 , NdGaO 3 , and LaGaO 3 also exhibited in-plane epitaxy, while f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…An interfacial Ba-Ca-Ti-O layer is also formed as a result of this interaction, but the superconducting film nevertheless has a strong epitaxial relationship with the substrate lattice [109]. Holstein et al observed a similar chemical interaction between Tl(2212) thin films and SrTiO 3 substrates [115]; however, in a crosssectional TEM study of TBCCO films grown on SrTiO 3 substrates, Morosin et al [116] found no evidence of chemical interaction even though thalliation took place in air at 850 • C. There is thus no current consensus on the reactivity of this interface at high processing temperatures. Less surprisingly, no interaction has been observed between Tl(1223) thin films grown by in situ techniques and SrTiO 3 substrates [91,114] and this is attributed to the lower deposition temperatures (between 650 and 720 • C).…”
Section: Strontium Titanatementioning
confidence: 99%
See 1 more Smart Citation
“…An interfacial Ba-Ca-Ti-O layer is also formed as a result of this interaction, but the superconducting film nevertheless has a strong epitaxial relationship with the substrate lattice [109]. Holstein et al observed a similar chemical interaction between Tl(2212) thin films and SrTiO 3 substrates [115]; however, in a crosssectional TEM study of TBCCO films grown on SrTiO 3 substrates, Morosin et al [116] found no evidence of chemical interaction even though thalliation took place in air at 850 • C. There is thus no current consensus on the reactivity of this interface at high processing temperatures. Less surprisingly, no interaction has been observed between Tl(1223) thin films grown by in situ techniques and SrTiO 3 substrates [91,114] and this is attributed to the lower deposition temperatures (between 650 and 720 • C).…”
Section: Strontium Titanatementioning
confidence: 99%
“…One technologically important substrate material on which it is impossible to deposit TBCCO thin films is sapphire. During thalliation severe film-substrate interactions occur which result in the formation of an interfacial layer of BaAl 2 O 4 and a concomitant degradation in the superconducting properties of the films [115,119]. In addition, the non-orthogonal axes in the substrate have a large lattice mismatch with TBCCO and there is a large difference in the thermal expansion coefficients of the materials, which can lead to cracking of the films.…”
Section: Sapphirementioning
confidence: 99%
“…This study involved imaging the surface morphology and collecting EBSD data from several small regions (about 20 mm wide) at radial positions every 30 around the surface of the cylinder. The surface morphology everywhere consisted of flat, plate-like grains as observed in films grown on planar MgO [19]. EBSD analysis showed that the Tl-2212 plates grow on MgO cylinders with their c-axes everywhere roughly parallel to the substrate surface normal regardless of the angle made with the MgO [1 0 0] axis (see Fig.…”
Section: Tl-2212 Films On Cylindrical Mgo Substratesmentioning
confidence: 87%
“…MgO has a cubic crystal structure with a lattice parameter of 0.42 nm; about 10% misfit with the (a-b) plane of the tetragonal Tl-2212 phase (with a ¼ 0:385 nm). As a result of the large lattice misfit, Tl-2212 films grown on planar MgO substrates tend to have strong c-axis alignment with the surface normal, but no unique in-plane epitaxial relationship [17][18][19] and therefore the films contain high-angle grain boundaries.…”
Section: Substrate Selectionmentioning
confidence: 99%
See 1 more Smart Citation